Peter von Oertzen 1924-2008 : A Political and Intellectual Biography - Kufferath, Philipp, (Historical Materialism Book Series ;, 2025)
This exhaustive study traces Peter von Oertzen's transformation from a Berlin upbringing marked by Prussian traditions, conservative revolution, and National Socialism to his role as a Marxist and left-wing Social Democrat. It explores his dual impact as a political scientist and activist, detailing his influence in informal networks, journal projects, and trade union education initiatives. Navigating the SPD's delicate internal dynamics, Oertzen faced governmental responsibilities and conservative opposition while engaging in dialogue with various Marxist, council-socialist, and alternative left currents. Awarded the Niedersachsen State History Prize in 2018, this work offers unique insights into 20th-century left Social Democracy.